Ebola virus disease: Recent advances in diagnostics and therapeutics - Supriya Jagga (Asian Pacific Journal of Tropical Medicine, 2019)
Ebola virus disease (EVD) is associated with haemorrhagic fever in humans and nonhuman primates, with a high rate of fatality (up to 90%). Some outbreaks in human history have proven the lethality of EVD. The recent epidemic of 2014 and 2015 in West Africa was the deadliest of all time (11 284 deaths). To understand the transmission dynamics, we have reviewed the epidemiology of EVD to date. The absence of any licensed vaccines or approved drugs against Ebola virus (EBOV) further highlights the severity and crisis level of EVD. Some organizations (public and private) are making considerable efforts to develop novel therapeutic approaches or vaccines to contain the outbreak of EBOV shortly. Here, we summarized the various potential drugs and vaccines (undergoing multiple phases of clinical trials) that have arisen as an alternative against EBOV, and we highlighted the numerous issues and limitations hindering this process. Alternatively, an increasing focus on strengthening the medical and civic health structure could provide speedy benefits in containing the spread of EVD, as well as offer a resilient foundation for the deployment of novel drugs and vaccines to the affected countries, once such drugs and vaccines become available.